(untitled) (American Journal of Energy and Natural Resources, 2022)
Access to electricity, reliable energy supply, and environmental protection are key elements that support economic development around the world. In most of Sub-Saharan African countries, the production deficit is a key issue. In addition, the network is made of long distance power lines, leading to huge voltage drops and frequent power cuts in remote electrified areas. Most of these areas offer a wealth of micro hydro power potential. It hence happens that the development of such project in an environment not prepared should address many issues from the technical, the economic and the institutional point of view. The aim of this paper is to examine how we could contribute to the design and development of such a project while taking into account the related constraints. From the findings and the literature review, we have suggested for each core aspect how we might overcome some difficulties. Given the similarity of the network architecture in remote areas in Africa, we have focused on one 148 kW case study in Cameroon to illustrate the implementation of the results. We got a 6.5cents/kWh cost-effective project from an initial investment of 480 509USD with the need to use robust and simple equipment and the need to adjust the regulations. Since power cut is harmful and a hence issue for a grid connected plant, we have also designed an architecture to address this issue of load shedding from the grid.